Application of optimized Streptococcus thermophilus and Lactobacillus bulgaricus on coconut milk in the production of niyoghurt - DEWI YUNITA; ELSA VARIZKI; SYARIFAH ROHAYA; IRFAN IRFAN; MURNA MUZAIFA (Jurnal Natural, 2023)
This research aimed to optimize the growth of commercial yogurt starter cultures (Streptococcus thermophilus and Lactobacillus bulgaricus) on coconut milk before they were applied in the production of coconut yogurt, which is known as niyogurt or cocogurt. The research consists of three steps. Firstly, both microbes were grown on 100% cow’s milk and were analyzed for pH and total lactic acid bacteria (LAB) to examine the length of fermentation time. Secondly, both microbes were gradually grown on cow’s milk and coconut milk media, with samples ranging in combinations of the two kinds of milk from 100% milk to 100% coconut milk. Finally, the optimized starter cultures were then applied to niyogurt production. The results showed that the pH of the starter cultures obtained in 100% milk after 48 hours of fermentation was 4.41±0.04 for Streptococcus thermophilus and 4.44±0.03 for Lactobacillus bulgaricus. Meanwhile, the total lactic acid bacteria counts were 8.62±3.03 log cfu/ml for Streptococcus thermophilus and 9.55±2.22 log cfu/ml for Lactobacillus bulgaricus. These results showed that both commercial starter cultures need long periods to reach the targeted pH and total lactic acid bacteria (LAB) suggesting that enrichment was needed before commercial starter cultures were used. Furthermore, after analyzing six samples of growth on different ratios of milk and coconut milk, it was seen that both starters could grow optimally on 100% coconut milk. The total LAB after 24 hours of fermentation was 11.07 log cfu/ml with pH 4.05. Based on chemical and microbiological analyses, the characteristics of niyogurt have met Indonesia’s Standard for food consumption (SNI 2981:2009). The niyogurt consisted of 3.15% protein content, 8.3% fat content, 0.83% total acid, 0.76% mineral content, and 11.48 log cfu/ml total LAB.